DAMPAK KEANGGOTAAN KELOMPOK LUMBUNG PANGAN MASYARAKAT TERHADAP PENDAPATAN USAHATANI PADI DI KABUPATEN TAKALAR - Muh Tahir; Sri Murdiyati; Sitti Arwati (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2017)
This study aims to analyze the income of paddy farming in members and non-members of the community granary group, and to know the impact of the membership of the granary group on the income of paddy farming. This research was conducted in Bontoloe Village, Galesong Sub District, Takalar District, South Sulawesi Province. Sampling was done by two methods, first for sample of granary member using purposive sampling method, second fornon-member of granary using simple random sampling method. So the total sample in this study were 34 farmers. Data analysis used is the analysis of different test (t test) and multiple linear regression. The results showed that the income earned by farmer members of the granary group amounted to Rp 9,386,227.00, while the income earned by non-member farmers in the granary group was Rp 9,175,144.00. Differences in paddy production, revenue, and income levels between member farmers and non-members of the granary group based on t test proved not significantly different. Factors that significantly affect the income level of paddy farming are land area, paddy seed price, pesticide price, and labor wage. While the impact of membership of community granary group was not significant to the income of paddy farming. But simultaneously (land area, price of paddy seed, price of urea fertilizer, phonska fertilizer price, pesticide price, labor wage, dummy member) can affect paddy farming income of 84.99%.